Well-being in Belgium Beyond Happiness and Income - Capéau, Bart; Cherchye, Laurens; Decancq, Koen; Decoster, André; Rock, Bram De; Maniquet, François; Nys, Annemie; Périlleux, Guillaume; Ramaekers, Eve; Rongé, Zoé; Schokkaert, Erik; Vermeulen, Frederic (Economic Studies in Inequality, Social Exclusion and Well-Being, 2020)
XV, 188 p. 57 illus., 38 illus. in color.